Federalism in the Patch: Canada's Energy Industry and the Constitutional Division of Powers Energy Law Edition - Downey, Brendan; Martz, Robert; Chiswell, Paul G.; Salamucha, Ramona (Alberta Law Review, 2020)
Disclaimer: This summary was generated by AI based on the content of the source document.